2023
DOI: 10.1186/s13321-023-00764-2
|View full text |Cite|
|
Sign up to set email alerts
|

MOFGalaxyNet: a social network analysis for predicting guest accessibility in metal–organic frameworks utilizing graph convolutional networks

Mehrdad Jalali,
A. D. Dinga Wonanke,
Christof Wöll

Abstract: Metal–organic frameworks (MOFs), are porous crystalline structures comprising of metal ions or clusters intricately linked with organic entities, displaying topological diversity and effortless chemical flexibility. These characteristics render them apt for multifarious applications such as adsorption, separation, sensing, and catalysis. Predominantly, the distinctive properties and prospective utility of MOFs are discerned post-manufacture or extrapolation from theoretically conceived models. For empirical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…ML studies on zeolites, porous carbons, MOFs, COFs, and their composites generally predicted materials’ CO 2 adsorption and separation properties based on the easily accessible structural features of materials, such as surface areas and element types. New tools were developed to predict guest accessibility of any given MOF from the chemical features, the organic linkers, and the metal ions. , Recent efforts showed that introducing new descriptors can offer time efficiency and more accurate predictions. For example, energy-based descriptors, including Gibbs free energy and Boltzmann weighted energy distributions of xenon (Xe) and krypton (Kr) gases, were demonstrated to be more important for determining Xe/Kr selectivities of MOFs compared to their structural and chemical features .…”
Section: Discussionmentioning
confidence: 99%
“…ML studies on zeolites, porous carbons, MOFs, COFs, and their composites generally predicted materials’ CO 2 adsorption and separation properties based on the easily accessible structural features of materials, such as surface areas and element types. New tools were developed to predict guest accessibility of any given MOF from the chemical features, the organic linkers, and the metal ions. , Recent efforts showed that introducing new descriptors can offer time efficiency and more accurate predictions. For example, energy-based descriptors, including Gibbs free energy and Boltzmann weighted energy distributions of xenon (Xe) and krypton (Kr) gases, were demonstrated to be more important for determining Xe/Kr selectivities of MOFs compared to their structural and chemical features .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the growing amount of structural and simulation data is generating a great deal of enthusiasm for creating machine learning models capable of predicting the properties of new materials. Over the past few years, a series of classes of ML models (simple ML models for regression, convolutional neural networks, graph neural networks, and transformers for more complex data) have emerged, demonstrating their growing effectiveness in predicting properties such as adsorption uptakes in MOFs, see Figure . Authors typically concentrate on assessing their model’s performance using various metrics on a validation data set.…”
Section: Perspectivesmentioning
confidence: 99%